IMPLEMENTATION OF THE COOPERATIVE LEARNING MODEL TYPE SPONTANEOUS GROUP DISCUSSION (SGD) IN FIQH SUBJECT TO IPROVE STUDENT LEARNING OUTCOMES - Bustanuddin, Bustanuddin; Subakri, Subakri; Usriyah, Lailatul (Faculty of Administrative Science, Universitas Brawijaya, 2025)
Low student achievement in the subject of Fiqh at the junior secondary level (SMP) remains a major challenge in Islamic religious education. Monotonous learning methods, dominated by teacher-centered lectures with minimal active student involvement, have led to a lack of conceptual understanding of both normative and applicative Islamic teachings. This study aims to examine in depth the implementation of the Cooperative Learning model type Spontaneous Group Discussion (SGD) in the teaching of Fiqh at SMP Negeri 2 Kuta Badung, and to analyze its influence on improving student learning outcomes, particularly in the cognitive domain.The research method used is descriptive qualitative, with data collection techniques including direct classroom observation, interviews with teachers and students, and analysis of student learning outcome documents. The research subjects were eighth-grade students and Islamic Education (PAI) teachers at the school. The SGD model was implemented by spontaneously dividing students into discussion groups without formal planning. Each group discussed a selected Fiqh topic and presented their findings to the class. The process was facilitated by the teacher as a discussion guide.The findings reveal that the application of the SGD model promotes an interactive, participatory, and enjoyable learning environment. Students became more active, confident, and demonstrated increased understanding of the Fiqh material. The average student score increased significantly from 63.4 (pre-test) to 81.2 (post-test), with more than 80% of students achieving scores above the Minimum Mastery Criteria (KKM). Additionally, teachers experienced a positive shift in their role from information deliverers to learning facilitators. The model supports the principles of the Merdeka Curriculum, particularly in shaping learners who are critical thinkers, independent, and collaborative. In conclusion, the Cooperative Learning model type SGD is effective for Fiqh instruction as it enhances student achievement while also developing character and social skills relevant to contemporary educational demands. The study recommends broader implementation of the SGD model in schools and its integration into character-based and contextually religious lesson planning. These findings are expected to serve as a valuable reference for Islamic Education teachers, curriculum developers, and policy-makers in designing transformative, learner-centered education.